Implementation of a Digital-Based Early Safety Warning System Program on a Branch Logistics Company in Jakarta - Hamidya, Syifa Ula; Ardyanto, Yustinus Denny; Paskarni, Indriati (Universitas Trunojoyo Madura, 2022)
Lack of involvement in interventions to carry out observations and analysis that causes the conditions and behavior of employees at one of the logistics companies at the Jakarta branch. The research aims to reduce potential unsafe of conditions unsafe actions in the workplace environment. This process involves employees recognizing potential problems in the workplace within the procedures of observation, feedback, and employee behavior interventions. The methodology used in this study is a descriptive method to describe present or ongoing issues. This method allows for assessing a condition and program implementation to make further improvements in the future. There are still several obstacles in implementing the K3 Program (Safety, Health, and Environment), where the program is still being performed manually. BBS STAR program does not cover unsafe conditions and unsafe actions, so reporting workers to management regarding conditions at work still not optimal yet. Employees also have some difficulty reporting unsafe conditions and unsafe actions in the workplace. SEWS program can be a preventive step in the occurrence of potential danger. The quality of employees could increase with the habit of analyzing dangerous aspects of the workplace environment. Employees' involvement in the SEWS contribution program can also help establish moral consistency.Keywords: K3, Unsafe conditions and unsafe actions, SEWS Program